Pengaruh Gaya Hidup dan Media Sosial Terhadap Perilaku KonsumtifMahasiswa Pendidikan Ekonomi Nommensen 2025 dengan Literasi Keuangan Sebagai Variabel Intervening - Dayana Rebecca Tampubolon; Maria Angelika Magdalena Sihotang; Beta Ria Sitanggang; Grece Rebecca Br Sihombing; Tiara yulanda br.gultom; Erfina Salia Sihombing (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the influence of lifestyle and social media on the consumptive behavior of students in the Economic Education program at HKBP Nommensen University, with financial literacy as an intervening variable. The research method used is a quantitative approach, with data collected through questionnaires. The research sample consists of Economic Education students from the 2025 cohort. Data analysis is conducted using multiple linear regression and mediation testing. The results show that lifestyle and social media have a positive effect on consumptive behavior. However, financial literacy is able to mediate the relationship by reducing the level of consumptive behavior.